(untitled) - Cox, Steven M. (Boston, Massachusetts, 1998)
This is a practical overview that will show you how the criminal justice system is a dynamic network that influences and is influenced by various publics. It also helps reades explore and understand the effects of politics on the system's day-to-day operations, the role of discretion thoughout the system, and the public's influence- through elected officials and lobbying- on criminal justice agencies.
Keywords: Criminal justice, Administration of; United States